Investigating the Effect of Integrated STEM Activities on Summer School Students' STEM Interests and Opinions - Benek, Ibrahim; Donmez, Ismail (Cukurova Univ, 2024)
The purpose of this study is to examine the transformative effect of integrated STEM (Science, Technology, Engineering and Mathematics) activities implemented in summer school on students' interests and experiences in STEM fields. A mixed method approach including both qualitative and quantitative data sources was used in the study. STEM Interest Scale, interview form, diaries and field notes were used as data collection tools. While qualitative data enabled in-depth exploration of students' experiences, quantitative data provided empirical evidence of the impact of integrated STEM activities on students. The findings show that integrated STEM activities positively affect students' interest in STEM fields, their perceptions and experiences regarding STEM education. The research is in line with the Self-Determination Theory which shows that intrinsic motivation, interest, and autonomy are important elements that shape students' experiences with STEM activities. The results highlight the need to diversify STEM education practices and promote inclusiveness in summer schools to ensure the long-term effectiveness and sustainability of STEM programmes.
Keywords: STEM; Summer School; Integrated STEM; STEM Interest; Self-determination Theory